Synthesis, structure-activity relationships and biological evaluation of benzimidazole derived sulfonylurea analogues as a new class of antagonists of P2Y1 receptor - Bano, Sehrish; Hussain, Zahid; Langer, Peter; Weisman, Gary A.; Iqbal, Jamshed (Frontiers in Pharmacology, 2023)
The P2Y receptors are responsible for the regulation of various physiological processes including neurotransmission and inflammatory responses. These receptors are also considered as novel potential therapeutic targets for prevention and treatment of thrombosis, neurological disorders, pain, cardiac diseases and cancer. Previously, number of P2Y receptor antagonists has been investigated but they are less potent and non-selective with poor solubility profile. Herein, we present the synthesis of new class of benzimidazole derived sulfonylureas (1a-y) as potent antagonists of P2Y receptors, with the specific aim to explore selective antagonists of P2Y1 receptors. The efficacy and selectivity of the synthesized derivatives (1a-1y) against four P2Y receptors i.e., t-P2Y1, h-P2Y2, h-P2Y4, and r-P2Y6Rs was carried out by calcium mobilization assay. The results revealed that except 1b, 1d, 1l, 1m, 1o, 1u, 1v, 1w and 1y, rest of the synthesized derivatives exhibited moderate to excellent inhibitory potential against P2Y1 receptors. Among the potent antagonists, derivative 1h depicted the maximum inhibition of P2Y1 receptor in calcium signalling assay, with an IC50 value of 0.19 ± 0.04 µM. The potential of inhibition was validated by computational investigations where bonding and non-bonding interactions between ligand and targeted receptor further strengthen the study. The best identified derivative 1h revealed the same binding mechanism as that of already reported selective antagonist of P2Y1 receptor i.e., (1-(2- (2-tert-butyl-phenoxy) pyridin-3-yl)-3–4-(trifluoromethoxy) phenylurea but the newly synthesized derivative exhibited better solubility profile. Hence, this derivative can be used as lead candidate for the synthesis of more potential antagonist with much better solubility profile and medicinal importance.